Defiant Braceros : How Migrant Fought for Racial, Sexual & Political Freedom - Laureanne Rivard (Communiquer)
In her book Defiant Braceros, Mireya Loza puts into writing the collective, individual and institutional memories of the binational Bracero Program, that was set aside by Mexico, the United States and the institutions involved. These are the stories of workers who took part in this program while challenging the names and ideals that were meant to be projected through this program. The oral narratives reported by Loza reveal how the State Parties used their official discourses to create a class of cyclical workers migration, which, as of today, is more effervescent than ever before.